Development and Validation of a Knowledge Test on Scientific Walnut Cultivation (Indian Journal of Extension Education, 2025)
Knowledge is the foundation for shaping attitudes, encouraging adoption of innovations, and guiding logical decision-making. Since knowledge forms the first step in the innovation-diffusion process, followed by persuasion and attitude change. In 2024, a study was carried out in the Pulwama district of the Kashmir region of J&K UT to design a knowledge test for systematic walnut growers with the aim to assess their understanding of various production recommendations. The test was developed using standard psychometric methods to ensure accuracy and reliability. Initially, 32 knowledge-based statements were framed with the help of subject experts. Each statement was analyzed using the difficulty index and discrimination index, which helped identify the most suitable for effectively measuring farmers’ knowledge. Based on this analysis, 14 statements were retained for the final test. To check reliability, the split half method was applied, yielding a high reliability coefficient of 0.90, using the Spearman Brown prophecy formula. Furthermore, internal consistency was assured using Cronbach’s alpha, which gave a coefficient of 0.83. It confirmed that the knowledge test was both reliable and valid, making it a strong tool for evaluating the knowledge of walnut growers.